Analisis Tingkat Literasi Keuangan Syariah Mahasiswa Generasi Z - Andrean Dzulhijrah; Diana Nur’azzah; Milasiti Nursadiyah; M. Zaky Khaerul Rijal; Zahwa Nur Hasya; Welsi Damayanti (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
The development of the Islamic economy globally continues to show an encouraging increase. However, in Indonesia, Islamic financial literacy and inclusion are still relatively low. One of the main challenges is the gap between theoretical understanding and application of Islamic financial products, especially among Gen-Z students. This study aims to evaluate students' level of knowledge about Islamic finance and their tendency to manage their personal finances, as well as identify factors that hinder the use of Islamic financial services. This study used a descriptive qualitative method with data collection techniques through questionnaires. A total of 77 students from Universitas Pendidikan Indonesia (UPI) became respondents in this study. The results obtained show that although students have a fairly good level of literacy and high interest in the Islamic financial system, it has not been followed by real practice in everyday life. The findings emphasize the need to increase educational efforts, utilize digital media more effectively, and strengthen the accessibility of Islamic financial services among the younger generation.